Prospective, randomized, crossover study to evaluate the benefit of human chorionic gonadotropin-timed versus urinary luteinizing hormone-timed intrauterine inseminations in clomiphene citrate-stimulated treatment cycles - Zreik, Tony (1999)
Objective: To compare two methods of timing IUI, urinary LH monitoring and transvaginal ultrasonography/hCG timing of ovulation, in patients receiving clomiphene citrate. Design: Prospective, randomized, crossover study. Setting: Yale University Reproductive Medicine Center. Patient(s): Infertile couples undergoing IUI because of unexplained infertility, anovulation, or male factor infertility. Intervention(s): Patients received clomiphene citrate on days 3–7 of the menstrual cycle and were randomized initially to one of two monitoring protocols. In protocol A, urinary LH monitoring was used to time IUI. Urinary LH levels were determined daily with the use of commercial kits, starting on day 10 of the cycle. When urinary LH was detected, IUIs were performed daily for the next 2 days. In protocol B, ultrasound monitoring of folliculogenesis was performed until a leading follicle of ≥18 mm was noted, at which time hCG (10,000 IU) was given intramuscularly and IUIs were performed daily for the next 2 days. If no pregnancy occurred, the couple crossed over to the alternate protocol for the next cycle and continued this alternating therapy for a total of four cycles. Main Outcome Measure(s): Pregnancy rate per cycle. Result(s): One hundred forty-one cycles were completed. In these cycles, six pregnancies occurred, for an overall pregnancy rate of 4.26% per cycle. The pregnancy rate with LH-timed IUI was 4.29% (3/70) and that with hCG-induced ovulation was 4.23% (3/71); the difference was not statistically significant. Conclusion(s): Timing IUI with the use of a relatively expensive and time-consuming method such as ultrasound monitoring of folliculogenesis and hCG induction of ovulation does not appear to produce an increased pregnancy rate over urinary LH monitoring of ovulation.